Development of Batempo Dance in Koto Padang Village, Tanah Kampung Sub-district, Sungai Penuh City - Rahmaini, Desi; Darmawati (Universitas Negeri Padang, 2023)
This study aims to describe the development of Batempo dance in Koto Padang Village, Tanah Kampung District, Sungai Penuh City, Jambi Province. The type of research used is qualititave research with descriptive analysis method. The object of research is the Batempo dance which is located in Koto Padang, Tanah Kampung District, Sungai Penuh City, Jambi Province. The main instrument in this research is the researcher herself, while the supporting instruments used are stationery, camera, and flaskdisk. Data collection techniques carried out by literature study, observation, interviews, and documentation. The data analysis technique was carried out by collecting data, reducing data, and drawing conclusions. From this study, it was found that after efforts were made to develop the Batempo dance in terms og the quantity of dance performers, the goal of the development was achieved, namely the formation of a new group of dancers for the Batempo dance, in the sense that the first group of the Batempo dance has been replaced, so that with the formation of a new group of dancers the results from developing the quantity of dance performers is a form of effort to preserve the Batempo dance in Koto Padang Village, Tanah Kampung District, Sungai Penuh City, Jambi Province.